Moya Moya Disease in a Child: A Case Report - Jagdish P. Goyal; Sanjeev S. Rao; Sangita Trivedi (Case Reports in Neurological Medicine)
We report a case of 8-year-old female child who was admitted at our hospital with complaints of transient ischemic attacks and left-sided hemiparesis. On MR angiography, the child was diagnosed to have Moya Moya disease. Moya Moya disease is a rare cause of cerebral stroke in children. The patient was treated conservatively and referred to a higher centre for specific neurosurgery. Neurosurgical revascularization process leads to favourable outcome.